2021
DOI: 10.1080/07853890.2021.2019826
|View full text |Cite
|
Sign up to set email alerts
|

Transition to telemedicine and its impact on missed appointments in community-based clinics

Abstract: Background and objective The Coronavirus Aid, Relief, and Economic Security Act led to the rapid implementation of telemedicine across health care office settings. Whether this transition to telemedicine has any impact on missed appointments is yet to be determined. This study examined the relationship between telemedicine usage and missed appointments during the COVID-19 pandemic. Method This retrospective study used appointment-level data from 55 Federally Qualified H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Wide variation in insurance coverage for nonpharmacologic treatments for persons with cLBP is well-established [ 22 ] and financial concerns can be a barrier to accessing care [ 44 ]. Beyond financial considerations, the complexity of navigating the health care system, particularly in the COVID era, is a barrier to treatment attendance, especially for in-person care [ 45 , 46 ]. Barriers to treatment initiation and persistence due to motivation or ambivalence are described for persons considering CHIs [ 47 , 48 ] and in our team’s discussions with stakeholders emerged as likely barriers for individuals considering engaging in the OPTIMIZE trial interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Wide variation in insurance coverage for nonpharmacologic treatments for persons with cLBP is well-established [ 22 ] and financial concerns can be a barrier to accessing care [ 44 ]. Beyond financial considerations, the complexity of navigating the health care system, particularly in the COVID era, is a barrier to treatment attendance, especially for in-person care [ 45 , 46 ]. Barriers to treatment initiation and persistence due to motivation or ambivalence are described for persons considering CHIs [ 47 , 48 ] and in our team’s discussions with stakeholders emerged as likely barriers for individuals considering engaging in the OPTIMIZE trial interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine promotes cost effective care in the clinic setting: studies found it is strongly associated with fewer missed appointments, more equitable patient visit duration, and better physician schedule adherence [ 15 , 16 ]. Neurosurgeons have reported an increase in perceived efficiency and safety with the adoption of telemedicine in surgical neuro-oncology and even believe it could become the preferred modality of the subspecialty, perhaps in a hybrid system combining telemedicine and in-person care [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…[44] Beyond nancial considerations, the complexity of navigating the health care system, particularly in the COVID era, is a barrier to treatment attendance, especially for in-person care. [45,46] Barriers to treatment initiation and persistence due to motivation or ambivalence are described for persons considering CHIs, [47,48] and in our team's discussions with stakeholders emerged as likely barriers for individuals considering engaging in the OPTIMIZE trial interventions. Motivational interviewing is a counseling style for eliciting behavior change by helping persons to identify and resolve ambivalence about making a change.…”
Section: Discussionmentioning
confidence: 99%